Maximum Bleaching of Vegetable Oils by Acid-Activated Bentonite: Influence of Nanopore Radius - Müsęerref Önal; Yüksel Sarıkaya (Adsorption Science & Technology)
The optimum conditions necessary for preparing a bleaching earth (BE) with maximum bleaching power (BP) towards soybean oil (SO) and cottonseed oil (CSO) were investigated. BEs were obtained by H 2 SO 4 activation of a white calcium bentonite (CaB) sample from the Kütahya region of Turkey. After drying for 4 h at 105 °C, the CaB samples were activated by heating their acidic aqueous suspensions for 6 h at 97 °C, the acid content of the dry bentonite/acid mixture being varied in the 0–70% mass range. The respective specific surface area (S) and specific nanopore volume (V) of the BEs were determined from nitrogen adsorption/desorption data obtained at −196 °C. For natural CaB, the values of S and V were 44 m 2 /g and 0.11 cm 3 /g, respectively. These values attained a maximum of 135 m 2 /g and 0.30 cm 3 /g for the BE sample prepared employing 40% H 2 SO 4 for acid activation. Interestingly, the maximum BP was not associated with the maximum S and V values. The optimum values for the percentage H 2 SO 4 , S and V for attaining the maximum BP were 20%, 100 m 2 /g and 0.17 cm 3 /g, respectively. The mean nanopore radius (r) of each BE was calculated using the corresponding S and V values. Nanopores with a mean radius in the range 3.5–5.5 nm, which was close to the diameter of the coloured pigment, were found to be mostly responsible for the BP towards SO and CSO. The results obtained in the present study indicate that the value of r was more effective than the S and V values of BEs in the bleaching of vegetable oils. Adsorption of a pigment onto a BE was found to depend not only on the physicochemical interaction between the pigment molecule and the BE surface, but also on the mean nanopore size.